MiR-125b-5p and miR-100-5p as Biomarkers and therapeutic targets for the prevention of particulate matter-induced non-smoker lung cancer - Moe Thi Thi Han; Tay Zar Myo Oo; Busayamas Chewaskulyong; Sakorn Pornprasert; Kanyamas Choocheep; Khanittha Punturee; Warunee Kumsaiyai; Yupanun Wuttiin; Sawitree Chiampanichayakul; Ratchada Cressey (PLoS ONE, 2025)
Non-smoking-related lung cancer is increasingly associated with environmental factors such as particulate matter (PM) exposure. Using deep small RNA sequencing, we identified distinct miRNA expression patterns in lung cancer patients compared to non-cancer controls, stratified by smoking status. Notably, hsa-miR-125b-5p and hsa-miR-100-5p were significantly downregulated in non-smoking lung cancer patients. Pathway enrichment analysis revealed smoking amplifies pathways related to glycan biosynthesis, signal transduction, and transcriptional regulation, while non-smoking lung cancer is characterized by immune dysfunction and metabolic alterations, including oxidative phosphorylation and natural killer cell cytotoxicity. Validation in a larger cohort using quantitative RT-PCR confirmed the suppression of miR-125b-5p and miR-100-5p in non-smoking lung cancer patients. Additionally, miR-203a and miR-199a-3p were identified as potential biomarkers for lung cancer, independent of smoking status. Chronic PM exposure in primary bronchial/tracheal epithelial cells initially elevated miR-125b-5p and miR-100-5p expression, but prolonged exposure suppressed these miRNAs while increasing their target genes, TXNRD1 and HOXA1 , suggesting stress-induced dysregulation. Functional studies using miRNA mimics demonstrated that miR-125b-5p and miR-100-5p suppress PM-induced cancer cell mobility and colony formation, with miR-125b-5p exhibiting broader effects. These findings underscore the critical roles of miR-125b-5p and miR-100-5p in PM-associated lung cancer progression and their potential as biomarkers and therapeutic targets. This study highlights distinct mechanisms of lung carcinogenesis in smokers and non-smokers, providing a foundation for targeted interventions in PM-associated lung cancer.